Persepsi Mahasiswa Pendidikan Agama Islam Terhadap Pembelajaran Online dan Kaitannya Dengan Tingkat Kecerdasan Spiritual - Mely Novasari Harahap (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study aims to explore the perceptions of Islamic Education students toward online learning and its contribution to students' social skills. Online learning is a form of technology-based educational innovation widely used in higher education. However, its implementation generates various perceptions among students, which are believed to influence their social abilities in interacting, communicating, and adapting within both academic and social environments. This research uses a quantitative approach with a correlational descriptive method. The research population is all students of the Islamic Religious Education Study Program, while the research sample is taken using specific sampling techniques according to the research needs. Data collection techniques are carried out through questionn aires, observations, and documentation. Data analysis uses validity and reliability tests, descriptive analysis, as well as correlation tests to determine the contribution of students' perceptions to the level of Spiritual Quotient. The research results indicate that the perception of Islamic Education students towards online learning falls into the fairly good category. Students assess that online learning provides easy access to materials and flexibility in study time, but there are still obstacles in interaction and understanding of learning materials. The analysis results show that there is a positive contribution between students perception of online learning and the level of Spiritual Quotient. The more positive the students perception of online learning, the better the level of Spiritual Quotient possessed by the students.